Loneliness and Depression among Adults with Visual Impairment - Fadillah Amrina (Sriwijaya Journal of Ophthalmology, 2022)
Loneliness has been termed a social epidemic, especially by people with disabilities; one of them is visual impairment. To our knowledge, no study has obtained specific estimates of depression for young and middle-aged adults with visual impairment (VI). These difficulties may be compounded by discrimination. Observational data revealed that those with sight loss were twice as likely as those with another impairment to have experienced discrimination. There is evidence that individuals with visual impairment have poorer mental health than their impairment-free counterparts. In health care settings, an association between visual impairment and depression has been consistently reported. Greater prevalence of depressive symptoms in those with visual impairment has also been reported. This study aimed to examine the prevalence of and factors associated with loneliness and depression in adults with visual impairment and examine its association with life satisfaction.